2016
DOI: 10.1039/c5cp06073g
|View full text |Cite
|
Sign up to set email alerts
|

Rotational spectroscopy of the atmospheric photo-oxidation product o-toluic acid and its monohydrate

Abstract: o-Toluic acid, a photo-oxidation product in the atmosphere, and its monohydrate were characterized in the gas phase by pure rotational spectroscopy. High-resolution spectra were measured in the range of 5-14 Hz using a cavity-based molecular beam Fourier-transform microwave spectrometer. Possible conformers were identified computationally, at the MP2/6-311++G(2df,2pd) level of theory. For both species, one conformer was identified experimentally, and no methyl internal rotation splittings were observed, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 66 publications
3
12
0
Order By: Relevance
“…Figure 6 summarizes their experimental methyl torsional barriers. Resembling cresols and methylanisoles (see Section 2.1.2.2 and Figure 5), microwave studies on three isomers of toluic acid have shown that the V 3 potential is so high in the o-isomer (molecule (3) in Figure 6) that no torsional splittings could be observed [156]. The barrier to methyl internal rotation drastically decreases in the meta- [157] and paraisomers [65].…”
Section: Carbonyl Substituent On the Ringmentioning
confidence: 99%
“…Figure 6 summarizes their experimental methyl torsional barriers. Resembling cresols and methylanisoles (see Section 2.1.2.2 and Figure 5), microwave studies on three isomers of toluic acid have shown that the V 3 potential is so high in the o-isomer (molecule (3) in Figure 6) that no torsional splittings could be observed [156]. The barrier to methyl internal rotation drastically decreases in the meta- [157] and paraisomers [65].…”
Section: Carbonyl Substituent On the Ringmentioning
confidence: 99%
“…QTAIM is a useful approach to evaluate the nature of hydrogen bond and its strength in addition to the geometrical analysis. [47,65] According to Bader's theory, the critical points (3,-…”
Section: Theoretical Detailsmentioning
confidence: 99%
“…Several molecular complexes involving carboxylic acids [3][4][5][6][7][8][9][10][11][12] have been investigated by rotational spectroscopy to understand the nature of their non-covalent interactions and to have information on their internal dynamics and on their conformational equilibria. Most attention has been paid to the complexes of carboxylic acids,mainly to their dimers [3] and to their adducts with water.…”
mentioning
confidence: 99%
“…Most attention has been paid to the complexes of carboxylic acids,mainly to their dimers [3] and to their adducts with water. [4] Plenty of data have been obtained on the dimers,c oncerning proton tunneling, [3a] the Ubbelohde effect, [3b] and conformational equilibria. [3c] HCOOH (FA) is the prototype of the carboxylic acids family and for this reason it is involved in most of the investigations of carboxylic acids with molecules containing other functional groups,s uch as its adducts with H 2 O, [4a] N(CH 3 ) 3 , [5] anhydrides, [6] thes implest aldehyde (CH 2 O), [7] the simplest amide (CH(CO)NH 2 ), [8] ethers (dimethylether), [9] ketones (cyclobutanone), [10] esters (isopropylformate), [11] and azines (pyridine).…”
mentioning
confidence: 99%